Preparation, characterization and reactivity ratios of copolymers 3-(trimethoxysilyl) propylmethacrylate and tris (methoxyethoxy) vinylsilane with N-vinylpyrrolidone and acrylamide - Mohammed, Ameen Hadi (2017)
The incorporation of two different monomers, having different physical and/or chemical properties, in the same polymer molecule in varying proportions leads to the formation of new materials with great scientific and commercial importance. The basic requirements for polymeric materials in some areas of medical applications are that they are hydrophilic, soft and oxygen-permeable. The aims of this work are to prepare and characterize four series of copolymers at low conversion, to determine the reactivity relationships of these copolymers, and to prepared and study properties of hydrogels that can be of some interest for medical purposes. Vinylsilane monomers (3-(trimethoxysilyl)propyl methacrylate (TMSPM) and tris (methoxyethoxy)vinyl silane (TMEVS)), N-vinyl pyrrolidone (NVP) and acrylamide (AM), were used to prepare the copolymers. TMSPM-co-NVP, TMEVS-co-NVP, TMSPM-co-AM and TMEVS-co-AM with different compositions were synthesized by free radical polymerization at low conversion using benzoyl peroxide (BPO) as initiator. The copolymers were characterized by Fourier Transform Infrared (FTIR)and Proton Nuclear Magnetic Resonance (1H-NMR), and their compositions were determined by elemental analysis. The monomer reactivity ratios were calculated by linearization methods proposed by Fineman-Ross and Kelen-Tudos, the intersection method proposed by Mayo-Lewis, and nonlinear method proposed by curve fitting procedure. The derived reactivity ratios (r1, r2) for TMSPM-co-NVP, TMEVS-co-NVP, TMSPM-co-AM and TMEVS-co-AM were: (3.722, 0.097), (0.504, 0.328), (1.872, 0.801) and (0.240, 1.242), respectively. The microstructure of copolymers and sequence distribution of monomers in the copolymers were calculated by statistical method based on the average reactivity ratios and found that results are in agreement with (r1, r2) values. No study has been reported on the copolymerization and reactivity relationships of hydrophobic monomers (TMSPM, TMEVS) with hydrophilic monomers (NVP, AM). Four series of TMSPM-co-NVP xerogels were prepared by bulk polymerization to ~100% conversion using BPO as initiator: (i) TMSPM/NVP copolymers covering a wide range of composition (10-90% NVP), (ii) TMSPM/NVP copolymers covering a wide range of composition (10-90% NVP), but all comprising a fixed content (1% w/w) of ethylene glycol dimethacrylate (EGDMA) as cross-linking agent, (iii) TMSPM30/NVP70 copolymers containing different concentrations (0-2%) of EGDMA, and (iv) TMSPM10/NVP90 copolymers containing different concentrations (0-4%) of EGDMA. The occurrence of translucency or opacity in some of the xerogels suggests the existence of more than one species, i.e. at least two polymers, which are immiscible. The transparency of xerogels and hydrogels could be enhanced by varying the concentration of EGDMA. The absence of EGDMA allows an easy diffusion of water molecules to the gel phase. The influence of the comonomer composition on equilibrium water content (EWC), weight loss, volumetric fraction of water (ᢥଵሻand linear expansion (ER) to hydration on the resultant hydrogels were investigated. All degree of swelling (with and without EGDMA) increased as the amounts of NVP in feed composition increased, this can be attributed to the hydrophilicity of NVP. More detailed investigations on effect of EGDMA on the properties of TMSPM30/NVP70 and TMSPM10/NVP90 were conducted. The swelling capacity and swelling parameters significantly decreased with increasing crosslinker content, due to the restrained mobility of the macromolecular chains. The mechanical properties of TMSPM30/NVP70 with (0-2%) EGDMA and TMSPM10/NVP90 with (0-4%) EGDMA xerogels were investigated using stress-strain test. Thermal analysis revealed that with an increase in EGDMA content, the glass transition temperature (Tg) increased, and weight loss decreased due to the restriction of the segmental mobility of the polymer chains. Oxygen permeability of hydrogels increases as TMSPM and water content increase. In conclusion, the reactivity ratios for four new copolymers; TMSPM-co-NVP, TMEVS-co-NVP, TMSPM-co-AM and TMEVS-co-AM have been determined. These copolymers possess new properties with potential use in different medical applications.